Improving Pedagogical Content Knowledge On Rational Numbers Of Cambodian Teacher Trainers - Leap Van; Sokalyan Mao; Veerle Cnudde (Global Education Review, 2018)
Despite adequate facilities and several education reforms, most Cambodian teacher trainers fail to provide sufficient content knowledge and student-centered pedagogy. Many also lack the skills to diagnose preservice teachers’ misconceptions and to propose adequate solutions. Dictating lessons with little feedback or applied activities or having pre-service teachers copy off the board for extended periods, suggests lowquality instruction (Tandon & Fukao, 2015). To tackle this, the Flemish Association for Development Cooperation and Technical Assistance (VVOB- education for development)1 developed a 3-year (20142016) programme in close collaboration with the Cambodian Ministry of Education, Youth and Sport (MoEYS). The programme was rolled out in all primary teacher training colleges (PTTCs). One of the interventions in this programme aimed at improving both Pedagogical Content Knowledge (PCK) and Content Knowledge (CK) on rational numbers of mathematics teacher trainers, with a focus on 1) mathematics content knowledge, 2) the use of representations to enhance pre-service teachers’ understanding, 3) assessing pre-service teachers’ learning, and 4) addressing misconceptions. A total of 54 mathematics teacher trainers participated in this intervention. Their capacity was built through training, coaching, mentoring and try-outs with pre-service teachers. The impact of the intervention was measured through a pre-test post-test design, enriched by qualitative data collected during 97 lesson observations. After the intervention, 91% of the teacher trainers had significantly increased their score on the PCK test and 94 % had improved their teaching strategy in at least two of the three criteria of PCK. In this paper, the design and impact of the intervention are explained, and suggestions for further research are provided.